Influence of tracking and pointing error on the performance of inter-satellite optical CDMA communication system - TAN Qing-gui; HU Yu; ZHAO Yue-ying (Tongxin xuebao)
In order to study the performance of inter-satellite optical CDMA communication system, the influence of tracking and pointing error on the BER of this communication system was analyzed. With considering the effects of multi-user interference, tracking, pointing error, and APD noise, the system model of inter-satellite optical CDMA com- munication system was presented. The relationship between BER and receiving optical power was analyzed in detail. The results show that the inter-satellite optical CDMA communication system can realize high-speed communication when the normal variance σ of tracking and pointing error is small. When σ is large, a new detection scheme and channel cod- ing should be used to improve communication performance.